NtbHLH49, a jasmonate-regulated transcription factor, negatively regulates tobacco responses to Phytophthora nicotianae - Wang, Wenjing; Zhang, Jianhui; Cao, Yi; Yang, Xingyou; Wang, Fenglong; Yang, Jinguang; Wang, Xiaoqiang (Frontiers in Plant Science, 2022)
Tobacco black shank caused by Phytophthora nicotianae is a devastating disease that causes huge losses to tobacco production across the world. Investigating the regulatory mechanism of tobacco resistance to P. nicotianae is of great importance for tobacco resistance breeding. The jasmonate (JA) signaling pathway plays a pivotal role in modulating plant pathogen resistance, but the mechanism underlying JA-mediated tobacco resistance to P. nicotianae remains largely unclear. This work explored the P. nicotianae responses of common tobacco cultivar TN90 using plants with RNAi-mediated silencing of NtCOI1 (encoding the perception protein of JA signal), and identified genes involved in this process by comparative transcriptome analyses. Interestingly, the majority of the differentially expressed bHLH transcription factor genes, whose homologs are correlated with JA-signaling, encode AtBPE-like regulators and were up-regulated in NtCOI1-RI plants, implying a negative role in regulating tobacco response to P. nicotianae. A subsequent study on NtbHLH49, a member of this group, showed that it’s negatively regulated by JA treatment or P. nicotianae infection, and its protein was localized to the nucleus. Furthermore, overexpression of NtbHLH49 decreased tobacco resistance to P. nicotianae, while knockdown of its expression increased the resistance. Manipulation of NtbHLH49 expression also altered the expression of a set of pathogen resistance genes. This study identified a set of genes correlated with JA-mediated tobacco response to P. nicotianae, and revealed the function of AtBPE-like regulator NtbHLH49 in regulating tobacco resistance to this pathogen, providing insights into the JA-mediated tobacco responses to P. nicotianae.